Desain dan Analisis Rangka Mobil Listrik Malem Diwa X.2 Model Prototype Menggunakan Metode Elemen Hingga - Iskandar Hasanuddin; Muhammad Tadjuddin; Hasan Akhyar; Mardhatillah Mardhatillah (Jurnal Teknik Mesin Unsyiah, 2019)
Supplies of fossil fuels as an energy source that is depleting became its own challenges in the provision of energy to the continuation of the future. One alternative is to become energy electrical energy. Study conducted in this study is meant to make the eco-friendly vehicles, one example is the electric car. Light vehicle weight and becomes a keyword in doing energy saving in everyday. The research was carried out using the element method to the frame of the car, with condition of load static – general. The software used in this study is ABAQUS. From the results stress result maximum stress of 1.972 x 105 Pa, maximum strain results of 2.592 x 10-6, while the displacement that occurred was of 2.858 x 10-7 m. Research results obtained that the car frame able to withstand loads given of 700 N, so that, it can be concluded that the framework of this car is secure against a given load.